Massive parallel sequencing as a new diagnostic approach for phenylketonuria and tetrahydrobiopterin-deficiency in Thailand - Chaiyasap P. (2017)
© 2017 The Author(s). Background: Hyperphenylalaninemia (HPA) can be classified into phenylketonuria (PKU) which is caused by mutations in the phenylalanine hydroxylase (PAH) gene, and BH4 deficiency caused by alterations in genes involved in tetrahydrobiopterin (BH4) biosynthesis pathway. Dietary restriction of phenylalanine is considered to be the main treatment of PKU to prevent irreversible intellectual disability. However, the same dietary intervention in BH4 deficien cy patients is not as effective, as BH4 is also a cofactor in many neurotransmitter syntheses. Method: We utilized next generation sequencing (NGS) technique to investigate four unrelated Thai patients with hyperphenylalaninemia. Result: We successfully identified all eight mutant alleles in PKU or BH4-deficiency associated genes including three novel mutations, one in PAH and two in PTS, thus giving a definite diagnosis to these patients. Appropriate management can then be provided. Conclusion: This study identified three novel mutations in either the PAH or PTS gene and supported the use of NGS as an alternative molecular genetic approach for definite diagnosis of hyperphenylalaninemia, thus leading to proper management of these patients in Thailand.